Economic impact of tourism in the coastal areas of Kelantan / Maimunah Sulaiman, Nafisah Safii and Abdullah Sudin Abdul Rahman - Sulaiman, Maimunah; Safii, Nafisah; Abdul Rahman, Abdullah Sudin (2004)
Records have shown that visitors or tourists to Kelantan would not miss to visit the coastal areas. Activities related to travel, hospitality is seen to have taken place in these areas, and local communities have depended on these activities as a source of income. With some hypothesis testing, there is a significant relationship between tourist spending and the tourists' income level as well as on their length of stay. The tests are consistent with the assumption that the higher the income of the tourist, the higher is their spending. The tests also proved that the length of stay also affects the tourist spending. A stay that is more than a day but not exceeding seven days would make the tourists spend more. The tourists engaged in some activities such as visiting beaches, eating, shopping and visiting towns but found that they spend most in shopping, accommodation, and eating. This expenditure is an important aspect of the study whereby it creates an income to the local community. Although the income give an economic impact to the community, but it does not stay long enough in the community to spur further development. This is so because I ocal supplier is not the m ajar supplier for most oft he tourists' products, ca using the income to leak from the community only after three rounds of community spending. This however, results in a weak multiplier effect that is about 30% of the income received in every round of spending.